A 90-day oral (dietary) toxicity and mass balance study of corn starch fiber in Sprague Dawley rats. (November 2016) - Crincoli, Christine M.; Nikiforov, Andrey I.; Rihner, Marisa O.; Lambert, Elizabeth A.; Greeley, Melanie A.; Godsey, Justin; Eapen, Alex K.; van de Ligt, Jennifer L.G.
Abstract: The potential toxicity of corn starch fiber was assessed and compared to polydextrose, a commonly used bulking agent with a long history of safe use in the food supply. Groups of male and female Crl:CD(SD) rats were fed 0 (control), 1, 000, 3, 000, or 10, 000 mg/kg-bw/day corn starch fiber in the diet for 90 days. The polydextrose reference article was offered on a comparable regimen at 10, 000 mg/kg-bw/day. Following a single gavage dose of [ 14 C]-corn starch fiber on study day 13 or 90, the mass balance of the test article was assessed by analysis of excreta samples collected from 0 to 168 h post-dose. There were no toxicologically or biologically relevant findings in any of the test article-treated groups. The few minor differences observed between the corn starch fiber and polydextrose exposed groups were considered to be due to normal biological variation. Following [ 14 C]-corn starch fiber dosing, nearly complete excretion of the administered dose occurred over 168 h post-dosing, with the majority excreted in the feces. The dietary no-observed-adverse-effect level of corn starch fiber after 90 days was 10, 000 mg/kg-bw/day. Similar toxicity profiles for corn starch fiber and polydextrose were observed due to the structural and compositional similarities of these materials. Highlights: Subchronic dietary administration of up to 10, 000 mg corn starch fiber/kg-bw/day to rats resulted in no adverse effects. The toxicity profile of corn starch fiber was comparable to polydextrose at an equivalent dose level. After [ 14 C]-corn starch fiber dosing, nearly complete excretion of the administered dose occurred over 168 h post-dosing.